FUNGSI IDENTIFIKASI CEK FISIK KENDARAAN BERMOTOR SEBAGAI UPAYA UNTUK MENGUNGKAP TINDAK PIDANA PENCURIAN - Jamalluddin, Jamalluddin (Universitas Ekasakti, 2022)
Article 64 and 65 of Law Number 22 Year 2009 concerning Road Traffic and Transportation, Part Seven Registration and Identification of Motorized Vehicles explains that every vehicle must be registered. This research is a legal research with a descriptive analytical specification. The function of identification of a motor vehicle physical check by the Pariaman One-Stop Manunggal Administration System in uncovering the crime of theft is as supporting evidence that proves that there is a relationship between evidence in the form of a motorized vehicle that is secured by investigators as the object of theft with the crime of theft being investigated. handled by investigators. The purpose of the physical check is as an effort to reveal crimes related to motorized vehicles because it is possible for the perpetrators to make combinations between the crime machines and vehicles that are physically unfit for use. Types of physical vehicle checks include the chassis and engine number because the chassis and engine number are the basis for making a Motorized Vehicle Registration Certificate and Proof of Ownership of a Motorized Vehicle. The mechanism for identifying physical checks of motorized vehicles as an effort to uncover criminal acts of theft by the Pariaman City One-Stop Manunggal Administration System are: 1) checking/checking the Vehicle Number Certificate (STNK) is matched with what is written in the vehicle documents with the outer physical condition of the vehicle such as type of vehicle, vehicle paint and so on. 2) Check the vehicle engine number. If the engine number contained in the STNK does not match the physical number on the vehicle engine, it can be concluded that there is a forgery or copying of the engine or vehicle. 3) Test vehicle.